Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Mobil Toyota Fortuner di Karawang - Nadia Riani Thadsyah; Reminta Lumban Batu (UNIVED Press, 2022)
In this developed era, Indonesian people need four-wheeled vehicles with more capacity. Therefore, in 2005, the Toyota Fortuner was introduced in Indonesia. Before making a purchase, consumers generally seek complete information about the product to be purchased and its alternative products. This study plans to decide the impact of cost and item quality on buying choices of Toyota fortuner. The strategy utilized in this study is a quantitative strategy with a non-likelihood testing method with purposive examining procedure on 100 individuals who purchase Toyota Fortuner items. The outcomes showed that cost affected buying choices for Toyota Fortuner, and item quality fundamentally affected buying choices for Toyota Fortuner. The finish of this study is that the cost and item quality both have positive and critical outcomes on buying choices.